Reproductive activity and biochemical composition of the pullet carpet shell Venerupis senegalensis (Gmelin, 1791) (Mollusca: Bivalvia) from Ria de Aveiro (northwestern coast of Portugal) - Joaquim, Sandra (2014)
The present study characterizes the reproductive cycle of Venerupis senegalensis (=V. pullastra) from Ria de Aveiro (Portugal) as well as its nutrient storage and exploitation strategy. The reproductive cycle followed a seasonal cycle that correlated negatively with sea surface temperature, and comprised a ripe stage in winter followed by a spawning period that began in late winter and ended in the early summer. This extended spawning may be an advantageous strategy for the species because it ensures a continuous supply of settlers. Gametogenesis began in late summer/early autumn and intensified with the decrease in temperature during autumn. The condition index increased even during the spawning period, which indicates that there is rapid recovery and that reserves are accumulated during late summer and used later in the gametogenic process. Proteins did not contribute significantly to gametogenesis and the glycogen pattern is typical of conservative species, since gametogenesis depends largely on the amount of glycogen stored. The lipid storage and utilization cycle showed that gametogenesis took place in autumn/winter and that energy reserves were accumulated in summer.